PEMBERLAKUAN ASAS CABOTAGE PERAIRAN SULAWESI TENGGARA BERDASAR-KAN INPRES JO UNDANG-UNDANG PELAYARAN - Beby Ansel Apriliya Imran; Elfrida Ratnawati Gultom (Fakultas Hukum Universitas Trisakti, 2022)
Indonesia has vast waters and the cabotage principle applies to connecting waters in Indonesia. The research’s problem: how to enforce cabotage principle in Southeast Sulawesi waters and how to empower Indonesian shipping in Southeast Sulawesi waters after cabotage principle enactment based on Presidential Instruction Number 5 of 2005 concerning Empowerment of the National Shipping Industry in conjunction with Law Number 17 of 2008 concerning Shipping. This research is normative and descriptive analytical legal research, using primary data to support secondary data, primary and secondary legal materials. The data is analyzed qualitatively and the conclusions drawn using deductive method. The conclusion is that the application of cabotage principle regulations in Southeast Sulawesi waters are going well, but cabotage principle has not carried out optimally. The positive impacts of cabotage principle implementation are: growing the country's economy, growing local companies, increasing the empowerment of human resources and reducing pollution and the negative impacts are in the form of a limited types of ships, one of which is mother vessels which are very few owned by Indonesia and because of this, the use of foreign ships is still being carried out due to the limited types of ships and high demand for services.